Sally Morgan: Aboriginal Identity Retrieved and Performed within and without My Place - Renes, Martín (Estudios Ingleses de la Universidad Complutense, 2010)
Sally Morgan’s auto/biography My Place (1987) played an important but contested role in recovering the indigenous heritage for Australia’s national self-definition when the country set out to celebrate the start of British colonisation with the Bicentennial (1988). My Place is strategically placed at a cultural and historical crossroads that has placated praise as well as criticism for its particular engagement with mainstream readership. indigenous and non-indigenous scholarship has pointed out how Morgan’s novel arguably works towards an assimilative conception of white reconciliation with an unacknowledged past of indigenous genocide, but two decades after its publication, the text’s ambiguous, hybrid nature may merit a more positive reading. A sophisticated merging of indigenous and non-indigenous genres of story-telling boosting a deceptive transparency, My Place inscribes Morgan’s aboriginality performatively as part of a long-standing, complex commitment to a re(dis)covered identity. On the final count, My Place’s engaged polyphony of indigenous voices traces a textual songline through the neglected and silenced history of the Stolen Generations, allowing a hybrid Aboriginal inscription of Sally Morgan’s identity inside and outside the text.